Dynamic target definition: a novel approach for PTV definition in ion beam therapy - Cabal Arango, Gonzalo Alfonso; Jäkel, Oliver (Radiotherapy and oncology, 2013)
Purpose - To present a beam arrangement specific approach for PTV definition in ion beam therapy. - Materials and methods - By means of a Monte Carlo error propagation analysis a criteria is formulated to assess whether a voxel is safely treated. Based on this a non-isotropical expansion rule is proposed aiming to minimize the impact of uncertainties on the dose delivered. - Results - The method is exemplified in two cases: a Head and Neck case and a Prostate case. In both cases the modality used is proton beam irradiation and the sources of uncertainties taken into account are positioning (set up) errors and range uncertainties. It is shown how different beam arrangements have an impact on plan robustness which leads to different target expansions necessary to assure a predefined level of plan robustness. The relevance of appropriate beam angle arrangements as a way to minimize uncertainties is demonstrated. - Conclusions - A novel method for PTV definition in on beam therapy is presented. The method show promising results by improving the probability of correct dose CTV coverage while reducing the size of the PTV volume. In a clinical scenario this translates into an enhanced tumor control probability while reducing the volume of healthy tissue being irradiated.
Gesehen am 28.01.2021